2019
DOI: 10.1016/j.biomaterials.2018.10.039
|View full text |Cite
|
Sign up to set email alerts
|

An affinity-based approach to engineer laminin-presenting cell instructive microenvironments

Abstract: Laminin immobilization into diverse biological and synthetic matrices has been explored to replicate the microenvironment of stem cell niches and gain insight into the role of extracellular matrix (ECM) on stem cell behavior. However, the site-specific immobilization of this heterotrimeric glycoprotein and, consequently, control over its orientation and bioactivity has been a challenge that has limited many of the explored strategies to date. In this work, we established an affinity-based approach that takes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…This demonstrates that PEGylation at 1:25 does not alter LM bioactivity. [34,37] 3D LM/PEG hydrogels were produced by mixing PEGylated LM (1:25) with a four-arm acrylate PEG and crosslinkers (either protease-degradable GCRDVPMSMRGGDRCG peptide (VPM) or PEG-dithiol (PEG-2SH)) (Figure 1B,C). LM distribution within the LM/PEG hydrogels was evaluated using immunofluorescence, showing a homogeneous distribution of the protein, whereas PEG-only gels did not show any staining (Figure 1D and Figure S2, Supporting Information).…”
Section: D Hybrid Laminin Hydrogels With Controlled Degradability and Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates that PEGylation at 1:25 does not alter LM bioactivity. [34,37] 3D LM/PEG hydrogels were produced by mixing PEGylated LM (1:25) with a four-arm acrylate PEG and crosslinkers (either protease-degradable GCRDVPMSMRGGDRCG peptide (VPM) or PEG-dithiol (PEG-2SH)) (Figure 1B,C). LM distribution within the LM/PEG hydrogels was evaluated using immunofluorescence, showing a homogeneous distribution of the protein, whereas PEG-only gels did not show any staining (Figure 1D and Figure S2, Supporting Information).…”
Section: D Hybrid Laminin Hydrogels With Controlled Degradability and Mechanical Propertiesmentioning
confidence: 99%
“…[9,[33][34][35] For example, hydrogels functionalized with fulllength LM111 take advantage of its multiple bioactive domains that bind components of the basal membrane such as nidogen, perlecan, agrin, and collagen IV to enhance nervous tissue regeneration (neurite growth and neural stem cell (NSC) differentiation). [33,[36][37][38][39][40] However, there are no studies that exploit the affinity of different GFs to various LM isoforms and their involvement in the organisation of different tissues. Moreover, LM may possess other domains that play a relevant role in the in vivo physiology of the cells, which cannot be mimicked in a short synthetic peptide and will still be functional when using the full-length protein.…”
Section: Introductionmentioning
confidence: 99%
“…17,[30][31][32] This straightforward method has proven effective for promoting cell attachment and proliferation and for triggering even more sophisticated responses, such as cell differentiation and tissue maturation. 17,33,34 The recent literature illustrates even more elaborate methods for engineering SyPs with ECM proteins. 17,[35][36][37][38] For instance, Barros et al 17 reported the design of SyP-ECM hydrogels for neural regeneration applications.…”
Section: Syps Functionalization To Promote Cell Attachment and Proliferationmentioning
confidence: 99%
“…(115−119) Indeed, this is evident in some of the studies reported in Table 1, which point out that the immobilization approach significantly affects laminin function. (116,118,119) Strategies explored to date, for full-length laminin immobilization have relied either on its transient noncovalent incorporation or physical entrapment (109,120−122) or, alternatively, on its nonselective covalent immobilization (110,111,115−117,120,123−126) by taking advantage of functional groups present in multiple sites of the laminin structure, such as amines and thiols (see Figure 5 for illustrative examples based on PEG hydrogels). While physical entrapment ensures no conformational changes of the protein due to Version: Postprint (identical content as published paper) This is a self-archived document from i3S -Instituto de Investigação e Inovação em Saúde in the University of Porto Open Repository For Open Access to more of our publications, please visit http://repositorio-aberto.up.pt/ A01/00 chemical conjugation, the absence of a stable binding may allow protein release by diffusion, especially in noncovalently cross-linked hydrogels.…”
Section: Hydrogels Functionalized With Full-length Lamininmentioning
confidence: 99%
“…To control the orientation of laminin while preserving the exposure of its multiple bioactive domains, we have recently explored an affinity-binding approach to immobilize laminin that takes advantage of the native high affinity interaction between the NtA and the coiled-coil domain of laminin. (118,119) When compared to the nonselective covalent immobilization,(118) the site-specific immobilization of laminin better preserved laminin bioactivity as evidenced by its enhanced ability to self-polymerize and mediate cell adhesion. Moreover, we showed the potential of affinity-bound laminin synthetic hydrogels, to be used as a dynamic 3D platform enabling human NSC proliferation, neuronal differentiation, and neurite extension.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%